Bridging the Great Divide: Musings of a Post-Liberal, Post-Conservative Evangelical Catholic - Barron, Robert (Rowman & Littlefield Publishers, 2004)
Bridging the Great Divide: Musings of a Post-Liberal, Post-Conservative Evangelical Catholic represents a pivotal moment in the life of the Catholic community. As the Church seeks to maintain its unique witness, nurture the faithful, and evangelize, a new generation of American Catholics has emerged. No longer the "next generation," these new leaders came of age after the Second Vatican Council and, like many others, no longer find compelling the battles between the liberals and conservatives throughout the post-conciliar period. Today's faithful are searching for an expression of Catholic Christianity that is vibrant, colorful, provocative, counter-cultural, deeply rooted in the tradition, and full of the promise of the Good News. In this timely and prophetic book, Father Robert Barron—himself a member of the younger generation—has minted a new vernacular and blazed a new way that goes bridges the great divide and gives voice to the concerns of post-liberal, post-conservative, evangelical believers.